2014
DOI: 10.3758/s13423-014-0767-2
|View full text |Cite
|
Sign up to set email alerts
|

Limits to the attentional boost effect: the moderating influence of orthographic distinctiveness

Abstract: The Attentional Boost Effect (ABE) refers to the counter-intuitive finding that the detection of infrequent targets in a divided-attention (DA) condition enhances memory of images co-occurring with targets (as compared with images co-occurring with distractors; Swallow & Jiang Cognition, 115, 118-132, 2010). Previous studies have shown that the ABE also applies to verbal materials (words; Spataro, Mulligan, & Rossi-Arnaud Journal of Experimental Psychology: Learning, Memory, and Cognition, 39, 1223-1231) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 25 publications
2
19
1
Order By: Relevance
“…We found little support for either prediction in our data. Notably, these conclusions are limited to the role of value in the attentional boost effect and do not call into doubt earlier work on the role of distinctiveness in the attentional boost effect Spataro et al, 2015). Unlike manipulations of value in this study, this earlier research demonstrated that items that were more distinct were also better remembered.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…We found little support for either prediction in our data. Notably, these conclusions are limited to the role of value in the attentional boost effect and do not call into doubt earlier work on the role of distinctiveness in the attentional boost effect Spataro et al, 2015). Unlike manipulations of value in this study, this earlier research demonstrated that items that were more distinct were also better remembered.…”
Section: Discussioncontrasting
confidence: 55%
“…However, little additional benefit may be incurred by pairing a valuable item with a target if both influence memory via the same mechanisms. Similar to manipulations of distinctiveness that reduce the magnitude of the attentional boost effect (cf., Mulligan et al, 2014; Spataro, Mulligan, & Rossi-Arnaud, 2015), the attention-to-value account predicts an under-additive interaction between item value and target detection. For this hypothesis to be supported, valuable items would need to be better remembered, and benefit less than neutral items from being paired with a target.…”
Section: The Present Studymentioning
confidence: 99%
“…However, the target-detection tasks in previous ABE studies usually involved the detection of surface perceptual features of a stimulus, and whether the ABE could be observed in detection tasks involving the detection of semantic information is unclear. To explore this question, the present study adopted the verbal paradigm of the ABE (Mulligan et al, 2014; Spataro et al, 2013, 2015), used Arabic numerals as semantic information in the detection tasks, and gradually increased the degree of semantic processing in the detection task over three experiments. The results showed that the target detection with semantic information (i.e., digits) also triggered the ABE (Experiment 1) and that the ABE could be extended to a more complex semantic judgement-based detection task (i.e., odd–even detection task) regardless of whether the detection task used a single-target stimulus (Experiment 2) or a multi-target stimulus (Experiment 3).…”
Section: Discussionmentioning
confidence: 99%
“…Experiment 1 adopted the classic dual-task paradigm of the ABE with verbal materials (Mulligan et al, 2014; Spataro et al, 2013, 2015). During encoding, a study word was presented above a briefly presented stimulus belonging to the detection task; the participants were asked to read the word aloud and try to remember the word while monitoring the predefined target stimulus and press the spacebar when they detected an infrequent target while making no response to frequent distractors.…”
Section: Methodsmentioning
confidence: 99%
“…Because previous evidence indicates that target detection requires more attention resources than distractor rejection (Duncan, 1980;Dux & Marois, 2009), the straightforward prediction would be that the recognition performance for target-paired words in the DA condition should be less accurate than the performance in the FA condition-in which participants are told to ignore the squares and focus all their attention on encoding the words. The ABE represents a surprising exception to this expected pattern because the recognition of target-paired stimuli in the DA condition either equals the level reached in the FA condition (producing a relative memory facilitation: Mulligan et al, 2014;Spataro et al, 2013Spataro et al, , 2015Swallow & Jiang, 2010) or exceeds it (producing an absolute memory facilitation: Prull, 2019;Spataro et al, 2013). Given its unusual nature, examining the conditions under which the effect can be shown and its boundary conditions represents an important issue.…”
mentioning
confidence: 98%